2012
DOI: 10.1111/j.1743-6109.2011.02568.x
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Sexual Function with the Prostatic Urethral Lift: A Novel Treatment for Lower Urinary Tract Symptoms Secondary to Benign Prostatic Hyperplasia

Abstract: Introduction We investigated the prostatic urethral lift, a novel, minimally invasive treatment for symptomatic lower urinary tract complaints presumed to be from benign prostatic hyperplasia (BPH), which aims to mechanically open the prostatic urethra without ablation or resection. We hypothesized that this novel approach would not degrade erectile or ejaculatory function. Aims We sought to determine the effect of the prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 23 publications
7
41
0
6
Order By: Relevance
“…The rapid and stable treatment response for LUTS with preservation of sexual function achieved by PUL has been confirmed in additional clinical trials [14,[20][21][22]. Indeed, a systematic review and meta-analysis were performed, confirming the therapeutic potential of PUL [23].…”
Section: The Evidencementioning
confidence: 93%
“…The rapid and stable treatment response for LUTS with preservation of sexual function achieved by PUL has been confirmed in additional clinical trials [14,[20][21][22]. Indeed, a systematic review and meta-analysis were performed, confirming the therapeutic potential of PUL [23].…”
Section: The Evidencementioning
confidence: 93%
“…Using several validated sexual function instruments in 40 patients undergoing PUL [ 92 ], there was minimal impact on erectile function and the majority of patients did not complain of retrograde ejaculation. Approximately 30-50 % of patients will require a postoperative catheter, hematuria and UTIs occur occasionally (<5 %), and fewer than 10 % of patients experience irritative symptoms.…”
Section: Complicationsmentioning
confidence: 94%
“…[25][26][27][28][29] Improvement in urinary symptoms, indicated by reduction in AUASI, has been consistent across the various studies, showing rapid relief within 2 weeks and sustained effect to 2 years ( Figure 5). Over 450 patient-years of data have been presented in peer-reviewed publications to date.…”
Section: The Urolift ò Systemmentioning
confidence: 96%
“…1,[32][33] Moreover, Woo et al demonstrated that, in addition to maintaining erectile function for men entering the study with no or mild ED, erectile function improved for men who entered the study with severe ED. 27 Building on the substantial evidence to date, additional studies are being undertaken. A second European randomized study is currently enrolling patients, a randomized study is planned in France, and open label studies are under way in several countries.…”
Section: S-6 Innovative Treatment For Bphmentioning
confidence: 99%